Enthalpy method for one dimensional heat conduction - Suraya Md Nasrudin, Farah; Mahadi, Shafaruniza (International Journal of Engineering and Technology, 2018)
In this paper, the Enthalpy Method is employed to compute an approximate solution of the system of nonlinear differential equations focusing on the simulation of moving boundary for one dimensional heat conduction. This paper is only considered in the problem of a technical grade paraffinâ€™s melting process. In order to seek the solution in term of temperature distribution, Finite Difference Method will be used. The results obtained are compared between solving with enthalpy and without enthalpy. The enthalpy method is more versatile, convenient, adaptable and easily programmable.Â Â